PTU-051 Donor morbidity following living donor liver transplantation (LDLT): outcome from a small volume centre. (28th May 2012) - Hakeem, A; Raza, S; Reddy, M; Jeffery, J; Hidalgo, E; Attia, M; Pollard, S; Toogood, G; Millson, C; Lodge, J P A; Prasad, K R
Abstract : Introduction: Living Donor Liver Transplantation (LDLT) has grown immensely in certain countries over the last few years, whereas in West the growth remains static and low volume. Donor morbidity following LDLT has been reported in the median range of 15%–30% in various studies. One of the limiting factor for the growth of LDLT has been the concerns with morbidity and mortality during a centres initial experience. We report the donor outcome from a small volume centre, so as to assess if there is an impact on volume with donor outcome. Methods: Between June 2007 and December 2011, 25 LDLT procedures were carried out in our unit. The criteria for donor selection included age, fitness for surgery and remnant liver volume. Donor demographics, graft type, complications, length of stay and overall survival were extracted. Donor morbidity was assessed objectively using the modified Clavien-Dindo classification. Continuous variables are expressed as mean ± SD. Results: The mean donor age was 38.4±11.0 years and donor BMI was 23.9±2.8 kg/cm 2 . Two donors were abandoned on table due to complex arterial and biliary anatomy respectively. The graft type was right lobe (n=12, 52.2%), left lateral lobe (n=10, 43.5%) and left lobe (n=1, 4.3%). The graft weight was 528.5±258.9 g. The morbidity was 21.7% (n=5). There were three Clavien grade II complications (wound infection, urinary infection and unknown sepsis needing antibiotics). One patient needed laparotomy for haemorrhage (Grade IIIb) and another patient had ultrasound guided drainage of subphrenic collection (Grade IIIa). None of our patients had any post-operative blood transfusion. The length of hospital stay was 7.9±2.8 days. At the end of median follow-up of 21.4 months, all our donors were alive, with no long-term morbidity. Conclusion: Our experience shows that donor hepatectomy for Living Donor Liver Transplantation is a safe procedure in a small volume unit. Our donor morbidity of 21.7% is comparable or better than most high volume centres across the world. Number of procedures performed by the unit shouldn't be an hindrance to the introduction of live donor liver programme. Competing interests: None declared.